Is prevention of acute pesticide poisoning effective and efficient, with Locally Adapted Personal Protective Equipment? A randomized crossover study among farmers in Chitwan, Nepal - Varma, Anshu; Neupane, ﻿﻿Dinesh; Ellekilde Bonde, Jens Peter; Jørs, Erik (La Medicina del Lavoro, 2016)
Background: Farmers’ risk of pesticide poisoning can be reduced with personal protective equipment but in low-income countries farmers’ use of such equipment is limited. Objective: To examine the effectiveness and efficiency of Locally Adapted Personal Protective Equipment to reduce organophosphate exposure among farmers. Methods: In a crossover study, 45 male farmers from Chitwan, Nepal, were randomly allocated to work as usual applying organophosphate pesticides wearing Locally Adapted Personal Protective Equipment or Daily Practice Clothing. For seven days before each experiment, each farmer abstained from using pesticides. Before and after organophosphate application, an interview surveys and blood tests were carried out, and analyzed with paired t-test, frequencies and percentages. Results: The difference between follow-up mean for acute organophosphate poisoning symptoms in the two groups was 0.13 [95% CI -0.22;0.49] and for plasma cholinesterase (U/ml) -0.03 [95% CI -0.11;0.06]. The difference between follow-up mean minus baseline mean for acute organophosphate poisoning symptoms in the two groups was 0.29 [95% CI -0.26;0.84] and for plasma cholinesterase (U/ml) -0.01 [95% CI --0.08;0.06]. Wearing the Locally Adapted Personal Protective Equipment versus Daily Practice Clothing gave the following results, respectively: comfort 75.6% versus 100%, sense of heat 64.4% versus 31.3%, other problems 44.4% versus 33.3%, likeability 95.6% versus 77.8%. Conclusion: We cannot support the expectation that our farmers in Chitwan, Nepal working with Locally Adapted Personal Protective Equipment would have fewer acute organophosphate poisoning symptoms, higher plasma cholinesterase (U/mL) and find it more efficient to work with the equipment than farmers working with their Daily Practice Clothing. Based on the farmers’ working behavior, compounds used, intensity and exposure duration we conclude that Locally Adapted Personal Protective Equipment does not provide additional protection during usual work practices. However, our Locally Adapted Personal Protective Equipment might offer protection from (certain) accidental overexposure. Trial Registration NCT02137317.